2002
DOI: 10.1093/ps/81.8.1136
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection and quantification of bursa of fabricius cellular proliferation or apoptosis in normal or steroid-treated neonatal chicks

Abstract: Apoptosis, or programmed cell death, is believed to be the mechanism for depletion of lymphocytes recognizing self-antigens following clonal expansion in the bursa of Fabricius. Although bursal apoptosis has previously been shown to increase following in vivo exposure to glucocorticoids, the microanatomical site of induced or normal apoptosis has not been unequivocally established. Presently, we adapted the existing terminal deoxynucleotidal transferase-mediated dUTP nick-end labeling (TUNEL) assay for use wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…(Rodríguez-Méndez et al, 2010) who demonstrated that there is a developmental wave of apoptosis in the bursa of white Leghorns associated with a greater abundance of TUNEL signals in both the cortical and medullar parts during the involution stage of this organ. In the present study, TUNELpositive cells were found in both the FAE and medulla, indicating that bursal lymphocyte apoptosis can clearly occur in both anatomical locations and closely resembles to that observed in chickens (Higgins et al, 2002). Compared to the present results previous study on cell apoptosis in in chickens and duck's lymphoid organs, the most prominent difference found is that apoptosis seems to be more extensive within the bursa than in the thymus.…”
Section: Discussionsupporting
confidence: 71%
“…(Rodríguez-Méndez et al, 2010) who demonstrated that there is a developmental wave of apoptosis in the bursa of white Leghorns associated with a greater abundance of TUNEL signals in both the cortical and medullar parts during the involution stage of this organ. In the present study, TUNELpositive cells were found in both the FAE and medulla, indicating that bursal lymphocyte apoptosis can clearly occur in both anatomical locations and closely resembles to that observed in chickens (Higgins et al, 2002). Compared to the present results previous study on cell apoptosis in in chickens and duck's lymphoid organs, the most prominent difference found is that apoptosis seems to be more extensive within the bursa than in the thymus.…”
Section: Discussionsupporting
confidence: 71%
“…Glucocorticoid-mediated immunosuppression is characterized by functional impairment or anatomical defects in immunobiological organs [15,20], peripheral blood lymphopenia and excessive apoptosis of thymic and bursal lymphocytes [17,20,27]. In order to evaluate the usefulness of IP-PA1 in controlling glucocorticoid-mediated immunosuppression in domestic chickens, we investigated the inhibitory effects of IP-PA1 on immunosuppression in dexamethasone-treated stressed chicken models in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its strong immune-enhancing effects in vitro, clinical application of LPS from pathological gram-negative bacteria such as Escherichia coli has been limited because they cause severe septic shock when large amounts enter the blood stream directly [17]. However, in contrast to injection, no toxicities of LPS have been reported when administered orally [22].…”
Section: Discussionmentioning
confidence: 99%
“…The bursa was sensitive to adrenal and gonadal steroid hormones which experimentally may cause its regression (Papermaster and Good, 1962;Erickson and Pincus, 1966;Freeman, 1971;Gasc et al, 1979;Le Douarin et al, 1980;Ylikomi et al, 1987;Wilson and Boyd, 1990;Mase and Oishi, 1991), or decrease the number of proliferating cells (Higgins et al, 2002). Research from the laboratory of Garcia-Espinosa et al, (2002) demonstrated the existence of a bursal anti-steroidogenic peptide (BASP) presenting structural homology to histone H1.…”
Section: Plical Epitheliummentioning
confidence: 99%